2007
DOI: 10.1002/dvdy.21190
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the signaling events that promote melanoma tumor cell vasculogenic mimicry and their link to embryonic vasculogenesis: Role of the Eph receptors

Abstract: During embryogenesis, the primordial microcirculation is formed through a process known as vasculogenesis. The term "vasculogenic mimicry" has been used to describe the manner in which highly aggressive, but not poorly aggressive melanoma tumor cells express endothelial and epithelial markers and form vasculogenic-like networks similar to embryonic vasculogenesis. Vasculogenic mimicry is one example of the remarkable plasticity demonstrated by aggressive melanoma cells and suggests that these cells have acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 93 publications
(105 reference statements)
2
69
0
2
Order By: Relevance
“…50,51 Hendrix and colleagues demonstrated that highly aggressive melanomas express VEcadherin, and that its function is central to the formation of vessel-like structures by melanoma cells. 36 They proposed that VE-cadherin promotes the interaction between focal adhesion kinase and EphA2 through regulation of EphA2's ability to translocate to the membrane. Interaction between EphA2 and its membrane-bound ligand would result in phosphorylation of EphA2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50,51 Hendrix and colleagues demonstrated that highly aggressive melanomas express VEcadherin, and that its function is central to the formation of vessel-like structures by melanoma cells. 36 They proposed that VE-cadherin promotes the interaction between focal adhesion kinase and EphA2 through regulation of EphA2's ability to translocate to the membrane. Interaction between EphA2 and its membrane-bound ligand would result in phosphorylation of EphA2.…”
Section: Discussionmentioning
confidence: 99%
“…This could then lead to melanoma vasculogenic mimicry via activation of MMP-2, finally resulting in cleavage of the laminin 5␥2 chain. 36 Interestingly, knock-down of VE-cadherin results in a dramatic redistribution of EphA2 on the cell surface, whereas EphA2 knockdown has no effect on VE-cadherin, 52 suggesting that VE-cadherin and EphA2 activation occurs sequentially and results in phenotypical changes in melanoma cells. Indeed, although we did not observe a decrease in the levels of EphA2 in C8161-c9 cells after Gal-3 silencing, this silencing nevertheless had a deleterious effect on the formation of tube-like structures by melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the regulation may work both ways. There is evidence that the integrity of E/VEcadherin-based adhesion between cells aids in the aggregation of EphA2 receptors along the cell membrane, enhancing receptor tyrosine phosphorylation (43)(44)(45).…”
Section: Regulation Of N-cadherin and ␤-Cateninmentioning
confidence: 99%
“…In melanoma, ephrin-A1-mediated activation of EphA2 and possibly other EphA receptors promotes proliferation (Easty and Bennett, 2000; Hess et al, 2007). Intriguingly, EphA2 has also been found to associate with vascular endothelial cadherin and promote the formation of blood vessellike structures by malignant melanoma cells, a role similar to that of EphA2 in tumor endothelial cells (see below).…”
Section: ) (Menges and Mccance 2007) Skin Cancer And Melanomamentioning
confidence: 99%